Formulation of imidazolium-based ionic liquids for methane hydrate dissociation - Sulaimon, A.A. (Society of Petroleum Engineers, 2020)
Formation of gas hydrates in oil and gas production systems constitutes a major flow assurance challenge and the consequences to the smooth production operation could be catastrophic. Recently, there is a shift of focus from total hydrate prevention to risk management which is more economical with reduced storage and injection facilities. Therefore, we have formulated two novel imidazolium-based Ionic Liquids (IM-based ILs) for thermodynamic methane hydrate inhibition. Heating, insulation, and addition of thermodynamic or kinetic inhibitors are strategies to prevent hydrate formation. The COnductor-like Screening MOdel for Realistic Solvents (COSMO-RS) was used to screen and rank several potential IM-based ILs based on their hydrogen bonding energies. 1-ethyl-3-methylimidazolium glutamate (EMIM-GMT), 1-butyl-3- methylimidazolium glutamate (BMIM-GMT) and 1-(3-cyanopropyl)-3-methylimidazolium glutamate (CPMIM-GMT) with hydrogen bonding energies of -62.01 KJ/mol, -61.46 KJ/mol and -67.21KJ/mol respectively were selected and synthesised for performance evaluation. Methane gas of 99.995 purity was used with deionised water to conduct thermodynamic dissociation tests using the SETARAM micro-Differential calorimetry (μDSC 7 Evo-1A). The μDSC was calibrated by comparing the offset dissociation temperature data of deionised water with published data from the literature. Thereafter, the dissociation profiles were obtained at pressures 30, 50, 75, 100, 125, and 150 bars. Results show that for 0.1wt of the three IM-based ILs, the dissociation temperature increases with pressure and a good thermodynamic inhibition with temperature shift in the range from 0.87 to 1.14°C was observed. The EMIM-GMT achieved the highest geometric average temperature shift of 1.14°C while the CPMIM-GMT and BMIM-GMT shifted the hydrate dissociation envelop by 0.91°C and 0.87°C respectively. Thus, the thermodynamic inhibition performance of EMIM-GMT is better than most of the current EMIM- and BMIM- Halide groups of IM-based ILs with the individual and combined average shift of less than 1.0°C. In this study, we have shown that the effectiveness of an IM-based IL as a thermodynamic methane hydrate inhibitor is largely a function of its hydrogen bonding energy between the water molecule and the IL ions. The relative order of performance of the three IM-based glutamate ILs is EMIM > CPMIM > BMIM. © 2020 Society of Petroleum Engineers - SPE Nigeria Annual International Conference and Exhibition 2020, NAIC 2020. All rights reserved.